Assessment of Drug Interaction Potential Between the Hepatitis C Virus Direct‐Acting Antiviral Agents Elbasvir/Grazoprevir and the Nucleotide Analog Reverse‐Transcriptase Inhibitor Tenofovir Disoproxil Fumarate. Issue 7 (7th June 2019) - Feng, Hwa‐Ping; Guo, Zifang; Caro, Luzelena; Talaty, Jennifer E.; Mangin, Eric; Panebianco, Deborah; Fandozzi, Christine; Zhu, Yali; Marshall, William; Huang, Xiaobi; Hanley, William D.; Jumes, Patricia; et al.
Abstract: Treatment of individuals coinfected with hepatitis C virus (HCV) and human immunodeficiency virus (HIV) requires careful consideration of potential drug‐drug interactions. We evaluated the pharmacokinetic interaction of the direct‐acting antiviral agents elbasvir and grazoprevir coadministered with the nucleotide reverse transcriptase inhibitor tenofovir disoproxil fumarate (TDF). Three open‐label, multidose studies in healthy adults were conducted. In the first study (N = 10), participants received TDF 300 mg once daily, elbasvir 50 mg once daily, and elbasvir coadministered with TDF. In the second study (N = 12), participants received TDF 300 mg once daily, grazoprevir 200 mg once daily, and grazoprevir coadministered with TDF. In the third study (N = 14), participants received TDF 300 mg once daily and TDF 300 mg coadministered with coformulated elbasvir/grazoprevir 50 mg/100 mg once daily. Pharmacokinetics and safety were evaluated. Following coadministration, the tenofovir area under the plasma concentration‐time curve to 24 hours and maximum plasma concentration geometric mean ratios (90% confidence intervals) for tenofovir and coadministered drug(s) versus tenofovir were 1.3 (1.2, 1.5) and 1.5 (1.3, 1.6), respectively, when coadministered with elbasvir; 1.2 (1.1, 1.3) and 1.1 (1.0, 1.2), respectively, when coadministered with grazoprevir; and 1.3 (1.2, 1.4) and 1.1 (1.0, 1.4), respectively, when coadministered with the elbasvir/grazoprevir coformulation. TDF had minimal effect on elbasvir and grazoprevir pharmacokinetics. Elbasvir and/or grazoprevir coadministered with TDF resulted in no clinically meaningful tenofovir exposure increases and was generally well tolerated, with no deaths, serious adverse events (AEs), discontinuations due to AEs, or laboratory AEs reported. No dose adjustments for elbasvir/grazoprevir or TDF are needed for coadministration in HCV/HIV‐coinfected people.